Response rates in low-stakes testing: insights from the Italian experience in large-scale assessments - Palmerio, Laura; Caponera, Elisa (Frontiers in Education, 2025)
Achieving high response rates in international large-scale assessments (ILSAs) is crucial for ensuring data validity and cross-national comparability. The first part of this article reviewed the literature on response rates in low-stakes assessments and showed that efforts to increase student motivation are central. In the second part, we described the strategies and practices developed by the Italian national center to enhance participation among schools, students, teachers, and parents in IEA surveys. A multi-dimensional approach was adopted, focusing on communication, training, logistical coordination, and data management. Early and clear engagement with school leaders and coordinators fostered commitment, while online seminars prepared staff and emphasized the importance of participation in international studies. A centralized platform streamlined communication and reduced the burden on schools, facilitating accurate sample tracking and data exchange. Teachers are encouraged to explain the significance of these studies to colleagues and students and to schedule assessment days thoughtfully to minimize absenteeism. When necessary, follow-up actions such as make-up sessions and personalized support for schools are provided. Special attention is dedicated to including students with special educational needs (SEN), emphasizing that certifications should not automatically lead to exclusion and that accommodations should be made whenever feasible. Customized communication strategies, logistical support, and privacy safeguards—particularly in handling parent questionnaires—are essential for securing engagement and trust. Overall, the Italian experience highlighted the importance of combining strong institutional support with thoughtful, flexible implementation strategies to maintain high levels of participation across all respondent groups.